Pendidikan Humaniora untuk Mengembangkan Wawasan Kemanusiaan dan Kebangsaan - H. Anwar Saleh Daulay (Universitas Negeri Malang, 2016)
Science and technology have given society many advantages, despite the fact that they also create certain anxiety. Humanistic education together with religious education could protect society from the negative effects of science and technology. With humanistic education, school will produce mature generation as human beings and good citizens rather than mere robotic workers. More well planned studies on all aspects of education need to be done to achieve the intended goal.